Common variants in toll-like receptor family genes and risk of gastric cancer: a systematic review and meta-analysis - Al Othaim, Ayoub; Al-Hawary, Sulieman Ibraheem Shelash; Alsaab, Hashem O.; Almalki, Sami G.; Najm, Mazin A. A.; Hjazi, Ahmed; Alsalamy, Ali; Firras Almulla, Abbas; Alizadeh, Hamzeh (Frontiers in Genetics, 2023)
Background: An increasing number of studies have suggested the relationship between single-nucleotide polymorphisms (SNPs) in toll-like receptor (TLR) genes and gastric cancer (GC) susceptibility; however, the available evidence is contradictory. This meta-analysis aimed to comprehensively evaluate whether the SNPs within the TLR family are related to GC development. Methods: PubMed, Scopus, and China National Knowledge Infrastructure (CNKI) were systematically searched up to May 2023 to obtain the pertinent publications. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were applied to examine the associations using the random-effects model. Results: A total of 45 studies with 25,831 participants (cases: 11,308; controls: 14,523) examining the relation of 18 different SNPs in the TLR family to GC were analyzed. Variations in TLR-4 rs4986790, TLR-4 rs4986791, TLR-5 rs5744174, and TLR-9 rs187084 were significantly associated with increased risk of GC in different genetic models. No significant association was detected for TLR-2-196 to -174de (Delta22), TLR-2 rs3804100, TLR-4 rs11536889, TLR-4 rs11536878, TLR-4 rs2770150, TLR-4 rs10116253, TLR-4 rs1927911, TLR-4 rs10983755, TLR-4 rs10759932, TLR-4 rs1927914, and TLR-10 rs10004195. Conclusion: These findings indicate that variations in TLR-4, TLR-5, and TLR-9 genes were found to be potential risk factors for GC.